A new species of the genus Pseudocrangonyx (Crustacea: Amphipoda: Pseudocrangonyctidae) from Simbok Cave, Korea - Lee, Chi-Woo; Tomikawa, Ko; Nakano, Takafumi; Min, Gi-Sik (Zootaxa, 2020)
A new subterranean species of pseudocrangonyctid amphipod, Pseudocrangonyx joolaei, is described from the groundwater of a cave in South Korea. Pseudocrangonyx joolaei sp. nov. can be distinguished from its congeners by the number of sternal gills as well as a combination of the antennal sinus, the accessory flagellum of antenna 1, and the terminal article of uropod 3. Molecular phylogenetic analyses based on nuclear 28S rRNA and histone H3, and mitochondrial cytochrome c oxidase subunit I and 16S rRNA genes revealed that P. joolaei sp. nov. formed a clade with P. akatsukai Tomikawa & Nakano, 2018 that inhabits limestone caves in the western Honshu island, Japan.